Increased neuroticism aggravates the risk of depressiye symptoms pregnant women - Podolska, Magdalena Z.; Majkowicz, Mikołaj; Bidzan, Mariola; Pankiewicz, Piotr; Sipak-Szmigiel, Olimpia; Podolski, Jacek (Studia Psychologica: Theoria et praxis, 2010)
The objective of this paper was to present personality traits and the role of personality factors in the pathogenesis of depression, as well as in predicting the incidence of depressive symptoms amongst women in pregnancy. The study involved 134 pregnant women (gestational age between 32 and 40 weeks, 50 ones with perinatal depression symptoms, and 84 Controls). In  creased neuroticism was revealed a factor aggravating the risk of depressive symptoms during pregnancy (OR=1.23). Pregnant women suffering from prenatal depression differed in their self assessment of real psychological needs but not with respect to ideał (expected) self image. These differences demonstrated their lack of self acceptance. In conclusion, some personality traits (such as neuroticism, introversion, a lower score of openness, agre  eableness and conscientiousness) and self assessment of real psychological needs are important psychological factors in the pathogenesis of depression, as well as in the prediction of the incidence of depressive symptoms amongst women in pregnancy